Socio-religious and socio-cultural perspectives of delayed marriage - Karamat Ayotola, Kelani; Karim, A.H.M Zehadul (SAVAP International, 2015)
Marriage is a social institution that is highly regarded but is in decline due to the impact of modernity. Marriage, meaning the institution regulating sex, reproduction, and family life (Brake, 2012) has generated much controversy in the contemporary world because of considerable variation in its meaning and practices. In this paper, we examine family and marriage as well as the interconnectedness between them from Western, cultural and religious context with reference to Islam. We discuss how modernity and modernization have impacted timing of marriage. Also, we discuss how the meaning of marriage has been redefined in the 21st century leading to changing marital practices such as delayed marriage. We provide explanation of delayed marriage using sociological theories. Furthermore, we provide understanding of delayed marriage from both cultural and Islamic perspectives. We then conclude that most cultures of the world as well as the religion of Islam vision of marriage and family are intolerant of delayed marriage